Rates of age‐ and amyloid β‐associated cortical atrophy in older adults with superior memory performance. Issue 1 (12th August 2019) - Dang, Christa; Yassi, Nawaf; Harrington, Karra D.; Xia, Ying; Lim, Yen Ying; Ames, David; Laws, Simon M.; Hickey, Martha; Rainey‐Smith, Stephanie; Sohrabi, Hamid R.; Doecke, James D.; Fripp, Jurgen; et al.
Abstract: Introduction: Superior cognitive performance in older adults may reflect underlying resistance to age‐associated neurodegeneration. While elevated amyloid β (Aβ) deposition (Aβ+) has been associated with increased cortical atrophy, it remains unknown whether "SuperAgers" may be protected from Aβ‐associated neurodegeneration. Methods: Neuropsychologically defined SuperAgers (n = 172) and cognitively normal for age (n = 172) older adults from the Australian Imaging, Biomarkers and Lifestyle study were case matched. Rates of cortical atrophy over 8 years were examined by SuperAger classification and Aβ status. Results: Of the case‐matched SuperAgers and cognitively normal for age older adults, 40.7% and 40.1%, respectively, were Aβ+. Rates of age‐ and Aβ‐associated atrophy did not differ between the groups on any measure. Aβ− individuals displayed the slowest rates of atrophy. Discussion: Maintenance of superior memory in late life does not reflect resistance to age‐ or Aβ‐associated atrophy. However, those individuals who reached old age without cognitive impairment nor elevated Aβ deposition (i.e. Aβ−) displayed reduced rates of cortical atrophy.